Professional Formation in the Gross Anatomy Lab and Narrative Medicine: An Exploration. (June 2016) - Kissler, Mark J.; Saxton, Ben; Nuila, Ricardo; Balmer, Dorene F.
Abstract : As an early and important experience in medical education, dissection in the gross anatomy lab is a locus of professional formation. Because students often think of their professional development in evolving, narrative terms, the authors propose that close attention to these narratives might add to understanding of professional formation in progress. They solicited written reflections from students, to explore ways that both the content and form of written reflections might illuminate themes relevant to professional formation, and to describe some elements of professional formation in the context of one institution (Baylor College of Medicine, Houston, Texas). Seventeen students participated in writing sessions and wrote in response to an oral interview transcript and to a poem. Using a reading approach that grew out of the narrative medicine movement, the authors collaboratively engaged the content and form of these written reflections. Students' collection of written reflections was a rich source of information about their experiences in the anatomy lab. Through both content (e.g., expressions of gratitude, transitions, self-awareness) and form (e.g., from less detailed writing to literary playfulness), their writings gave a glimpse into the tensions, disappointments, and satisfactions of the practice of gross anatomy. This project models one way that educators can read and respond to the reflective writing that students generate. The authors go on to propose ways that interactions around reflective writing can be part of a broader goal of forming narrative-minded physicians, who become increasingly self- and other-aware as they progress in their education and practice.